IMPRESI LINGKUNGAN ARTIFISIAL: Studi Kualitatif Tentang Persepsi Santri Pondok Pesantren Arrisalah Terhadap Lingkungan Artifisial - Aufia - Aisa (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2018)
Artificial environments began to attract the attention of aspiring students after many of the modern boarding school that began to adopt it as a superior material to form an artificial language environment. This study aims to find out how the perception of students of Arrisalah boarding school to the artificial environment that has been many discussed, so it is known how much the response of santri to the artificial environment. This research uses qualitative descriptive analysis. The research is described with words according to the respondent's opinion, what is in accordance with the research question, then analyzed also what is behind the respondent behave (thinking, feeling and acting). Keywords: perception of students, Artificial environment.